PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN PERTAMBANGAN - RONA TUMIUR MAULI CAROLIN SIMORANGKIR (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
This research aims to know the influence of return on asset, return on equity, and net profit margin on stock return. The population used Minning Company on the BEI with the observation periods during 2013 until 2017 as many as 13 companies. The source of the secondary data has been obtained from Indonesia Stock Exchange. The data analysis technique has been carried out by using multiple linear regressions analysis. Based on the result of the analysis indicate that return on asset, return on equity, and net profit margin significant effect on stock return of banking company. Based on the test results are partially, return on asset has a negative and significant effect on stock returns, return on equity and net profit margin have influence to the stock return of Minning Company.